Parametric synthesis of combined automatic regulating systems with digital PIDcontrollers - Kovela, Ivan; Ivaniuk, Oleg; Vlakh-Vyhrynovska, Galina; Stakhiv, Roman (Eastern-European Journal of Enterprise Technologies, 2017)
The problem of calculation of combined digital automatic regulation systems was considered. The main purpose of the study was to develop, on the basis of the principle of invariance, a method of parametric synthesis of combined systems with digital PID-controllers. To calculate the closed loop of the combined system taking into account the requirements to its stability and quality of regulation, the method of multicriterial parametric optimization was used. Conditions of physical realization of the ideal compensator on the basis of absence of a link with a negative net delay and ideal differentiating links in its transfer function were indicated. Choice of the structure of the transfer function of the real compensator was substantiated on the basis of coincidence of its complex frequency response with the complex frequency response of the ideal compensator at zero and operating frequencies. The results of synthesis of a combined system with a digital PID-controller and a real object have shown that the proposed method ensures quality of the digital system practically equivalent to that of the continuous system which is ensured by the choice of the structure of the discrete algorithm of the closed loop operation and the corresponding choice of the period of discreteness. In particular, it has been found that the use of the compensator enables an approximately fivefold reduction of the maximum dynamic deviation of the regulated value and approximately threefold improvement of the system dynamic precision according to integral absolute quality estimates. The developed approach can be applied for synthesis of combined systems with digital PID-controllers and a wide class of objects